WOMAN’S REBELLION IN WS. RENDRA’S BERSATULAH PELACUR-PELACUR KOTA JAKARTA POEM: FEMINISM APPROACH - Zainul Alim; Moh. Iskandar; Sri Utami Lestari (Jurnal Komposisi, 2019)
Literary works are the creative and imaginative writing. It is made as the communication and the reflection of life. There are some of literary works, such as poetry, drama, short story and novel. The literary works can be understood by the theory to interprate the meaning; literaly or figuratively. This study is about the sociology of literature. The problem of this study is how the condition of woman in Indonesia, especially Jakarta which was as a prostitudes reflected in WS. Rendra’s Bersatulah Pelacur-pelacur Kota Jakarta.  The object of this study is Bersatulah Pelacur-pelacur Kota Jakarta poem written by W.S. Rendra. It use Liberal Feminism perspective of Feminism Theory. The poem is the primary source of data and the secondary source of data is the other references or materials related with this research. This study is also belongs to qualitative research. The result of the study is to reveal the social conditions, society, and government of Indonesia which assumed that women was weak and contemptible by literary works. The outor wanted to tell how a prostitution which is basically forbidden to be legalized in Indonesia, even the government officials become the lovers of the world of prostitution.